2003
DOI: 10.1046/j.1365-3059.2003.00811.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the presence of R‐genes for resistance to late blight (Phytophthora infestans) of potato (Solanum tuberosum) on the underlying level of field resistance

Abstract: The differential genotypes R 1 , R 10 and R 11 , as originally defined by Black, were crossed with R-gene-free cultivars and the progenies divided into two subpopulations comprising those which had inherited the R-gene and those which had not. The underlying level of field resistance of the two groups was compared in a field trial in which they were inoculated with an isolate that could overcome the relevant R-genes. The R-gene-bearing group was significantly ( P < 0·001) more resistant than the R-gene-free gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(51 citation statements)
references
References 20 publications
2
45
0
4
Order By: Relevance
“…In fact, some researchers speculate that major genes are just very eVective alleles at QTLs and that the borders between the two traditionally distinguished types of resistance can be blurred (Gebhardt and Valkonen 2001). Also, R genes overcome by pathogen can still have some residual eVect, enhancing the quantitative resistance of the plant (Stewart and Bradshaw 2001;Stewart et al 2003). QTLs for the resistance components and length of vegetation period in our study only partially overlapped (Fig.…”
Section: Discussionmentioning
confidence: 69%
“…In fact, some researchers speculate that major genes are just very eVective alleles at QTLs and that the borders between the two traditionally distinguished types of resistance can be blurred (Gebhardt and Valkonen 2001). Also, R genes overcome by pathogen can still have some residual eVect, enhancing the quantitative resistance of the plant (Stewart and Bradshaw 2001;Stewart et al 2003). QTLs for the resistance components and length of vegetation period in our study only partially overlapped (Fig.…”
Section: Discussionmentioning
confidence: 69%
“…Although planted in small quantities, many of these would seem to have a stable, race-nonspecific resistance, but there is evidence that some have a combination of race-specific (R-gene) and horizontal resistance. Stewart et al (2003) suggested that increased resistance was conferred by defeated R-genes or linked genes for field resistance. In seasons and at locations where disease pressures remained low, these resistant varieties have been grown and have yielded well without protection and are therefore of interest to organic farmers, particularly if varieties have high levels of tuber-blight resistance.…”
Section: Ukmentioning
confidence: 99%
“…Genetic analysis suggests that the defense mechanisms underlying both resistance phenotypes are similar. R genes as well as genes with sequence similarity to R genes, defense signaling genes as well as defense response genes, may play a role in quantitative resistance to P. infestans (Leonards-Schippers et al 1992, 1994Trognitz et al 2002;Stewart et al 2003;Pajerowska et al 2005;Tan et al 2008). Introgression of R genes from the wild species Solanum demissum into cultivated potato failed to equip cultivars with durable resistance in the field, because the HR type of resistance was soon overcome by new, virulent P. infestans races.…”
mentioning
confidence: 99%